RUSSIAN JUDGES AND HIGHER LEGAL EDUCATION: HISTORICAL ASPECT - Dmitry O. Serov (Высшее образование в России)
The article is devoted to the history of the formation in the Russian legislation of thequalification requirement for judges to have the higher legal education. The analysis of the normative acts is carried out in conjunction with the brief consideration of the question of the development of legal education in Russia in XVIII–XX centuries. The author provides the sample data on the educational level of Russian judges for the years 1851–1990.